Torque Performance of Permanent Magnet Synchronous Motor based on Different Rotor Structures - Talip, Firdaus; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2023)
Permanent magnet synchronous motor (PMSM) consists of permanent magnet at the rotor to produce a constant magnetic field. Permanent magnet synchronous motor classified into two categories which is Interior Permanent Magnet Synchronous Motor (IPMSM) and Surface Permanent Magnet Synchronous Motor (SPMSM). For IPMSM, a permanent magnet is embedded inside the rotor core while for SPMSM, the permanent magnet is attached at the surface of the rotor. IPMSM offers high torque and power density. However, it produces high cogging torque compared to SPMSM. The performances of IPMSM are also related to the permanent magnet materials that are used to produce constant magnetic flux for the motor. In this paper, the design study of 4 pole 24 slots with different rotor structure parameters is studied to compare the torque performances with the same type of permanent magnet materials. The permanent magnet materials that have been selected are Neodymium Iron Boron (NdFeB). Initially, design procedures of IPMSM including parts drawing, material and condition setting, the properties setting are all explained. Then, a coil arrangement test is conducted to perform 3 phase armature coil arrangement. Finally, the purpose of this paper is to find out which rotor structure can produce higher performance.